2017
DOI: 10.21825/vdt.v86i4.16183
|View full text |Cite
|
Sign up to set email alerts
|

Fysiologische effecten van verschillende soorten arbeid op de spierontwikkeling van het paard

Abstract: It is well known that exercise induces chemical, metabolic and structural changes in muscles. However, the effect of the type of exercise on these changes has not been thoroughly studied in horses yet, because of a lack of standardized study methods. In this review, the effect of three different types of exercise on muscle adaptation and metabolic responses is investigated. The requirements for power exercise are not the same as for low intensity exercise. Each type of training induces its own shift in muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Increase in blood lactate after high intensity short duration exercise was also observed in horses shortly after vaquejada (BINDA et al, 2016;SOUZA et al, 2019), barrel racing (RODRIGUES et al, 2016;SOUZA et al, 2018;GOMES et al, 2019;GOMES et al 2020a;Gomes et al, 2020b) and double roping (PEREIRA et al, 2018). Increase in lactic acid can lead to fatigue or early muscle damage and is more common in athletes little conditioned to the type of exercise (VERMEULEN et al, 2017). However, some studies have shown that this increase happening in equines adapted to high intensity short duration exercise, but who showed a considerable reduction in lactate after rest, but who showed a considerable reduction in plasma lactate after resting for 30 min.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Increase in blood lactate after high intensity short duration exercise was also observed in horses shortly after vaquejada (BINDA et al, 2016;SOUZA et al, 2019), barrel racing (RODRIGUES et al, 2016;SOUZA et al, 2018;GOMES et al, 2019;GOMES et al 2020a;Gomes et al, 2020b) and double roping (PEREIRA et al, 2018). Increase in lactic acid can lead to fatigue or early muscle damage and is more common in athletes little conditioned to the type of exercise (VERMEULEN et al, 2017). However, some studies have shown that this increase happening in equines adapted to high intensity short duration exercise, but who showed a considerable reduction in lactate after rest, but who showed a considerable reduction in plasma lactate after resting for 30 min.…”
Section: Resultsmentioning
confidence: 94%
“…In this process, lactic acid is produced and accumulated, and the muscle glycogen is quickly exhausted, both with consequences for the glycogen. A horse breed that is outstanding for these requirements is the quarter horse, mainly because it has IIX type muscle fibers, that contract quickly, are good for glycogen storage (VERMEULEN et al, 2017), have low oxidative capacity and high glycolytic capacity that favor the execution of this exercise (LOPES et al, 2009;RODRIGUES et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In horse sports where there is high intensity and short duration exercise, the organism intensifies anaerobic mechanisms, mainly the anaerobic glucose (BARBOSA et al, 2016), due to the need for rapid production and uptake of energy to give energetic support to the muscule work (VERMEULEN et al, 2017). Vaquejada is among the sports where anaerobic mechanisms are needed by the horses´ organism.…”
Section: Introductionmentioning
confidence: 99%
“…During prolonged exercise energy needs are met through lipolysis and, to a lesser extent, gluconeogenesis (GUYTON and HALL, 2016). Therefore, changes in blood lipid concentrations serve as an indicator of changes in energy metabolism (VERMEULEN at al., 2017). Furthermore, strenuous exercise in racehorses elevates blood NEFA, triglyceride and cholesterol concentrations, in contrast to riding horses, due to the better adaptation of riding horses to lipid mobilization (LI et al, 2012).…”
Section: Introductionmentioning
confidence: 99%